Pembuatan Karya Seni Menggambar Dekoratif pada Caping dalam Mata Pelajaran SBK Siswa SD Kota Bengkulu - Helce Marisa Putri; Hasnawati Hasnawati; Nani Yuliantini (JURIDIKDAS, 2019)
This study aims to describe the process of making and drawing decorative work of caping in the subjects of Art Culture and Skills (SBK) class III A SD Negeri 07 Kota Bengkulu. The type and method of this research is skin research and descriptive method with participant observation technique. The research subjects were all students of class III A SD Negeri 07 Kota Bengkulu which amounted to 31 people. The research instrument is a human instrument, using obsevation guidelines, interview guides, and guidelines of the work. Data collection techniques such as observation, interview, and documentation / work. The data analysis of the process of making works is done by studying the data and then reducing, display, and drawing conclusions. Analysis of the work data will be discussed by looking at the elements and principles of art that exist. The process of making six works of decorative drawing art on the caping begins with a discussion determines the motive to be chosen in making the work. Followed by preparing tools and materials. After that give the basic paint on the caping. Selanjunya make motif design and thicken motifs and then coloring motifs. Six pieces of artwork drawing decorative on the caps made students contain elements and principles of fine art that contains elements of lines, fields, and colors. Placement of these motives on the caping contains the principles of art that is the principle of unity, balance, rhythm, emphasis and harmony.This study aims to describe the process of making and drawing decorative work of caping in the subjects of Art Culture and Skills (SBK) class III A SD Negeri 07 Kota Bengkulu. The type and method of this research is skin research and descriptive method with participant observation technique. The research subjects were all students of class III A SD Negeri 07 Kota Bengkulu which amounted to 31 people. The research instrument is a human instrument, using obsevation guidelines, interview guides, and guidelines of the work. Data collection techniques such as observation, interview, and documentation / work. The data analysis of the process of making works is done by studying the data and then reducing, display, and drawing conclusions. Analysis of the work data will be discussed by looking at the elements and principles of art that exist. The process of making six works of decorative drawing art on the caping begins with a discussion determines the motive to be chosen in making the work. Followed by preparing tools and materials. After that give the basic paint on the caping. Selanjunya make motif design and thicken motifs and then coloring motifs. Six pieces of artwork drawing decorative on the caps made students contain elements and principles of fine art that contains elements of lines, fields, and colors. Placement of these motives on the caping contains the principles of art that is the principle of unity, balance, rhythm, emphasis and harmony.